Preferensi Abu Dawud Sulaiman Bin Najjah dalam Kaidah Rasm Al-Mushaf / Preference of Abu Dawud Sulaiman Bin Najjah In Rules of Rasm Al-Mushaf - Ibnu Rawandhy N. Hula (Diwan : Jurnal Bahasa dan Sastra Arab, 2020)
تناول هذا البحث  اختيارات أبو داود سليمان بن نجاح في قواعد رسم المصحف التي تم تحليلها من كتابه الأثري "مختصر التبيين لهجاء التنزيل". ،يستخدم كتاب المصحف كتابه وتأليفه مفهومه في علم رسم المصحف وجعلوه كمرجع رئيسي ومصدر أساسي في تثبيت معظم أنماط نسخ وكتابة الحروف و الكلمات القرآنية الصعبة والمتنوعة والمعقدة , حتى تكون آراءه تختلف كثيرة بعمل وعلم أستاذه (أبو عمّار الدّاني - المقنع). ومن مزايا كتابه (التنزيل) أنه تم تأليفه وترتيبه بالطريقة التحليلية من سورة الفاتحة إلى الناس, بحيث يكون متواصلًا ومفصلاً وشاملاً وسهلًا في المعلومات عن نسخ ورسم القرآن. هذا البحث دراسة شخصية رائعة بحيث تكون الطريقة المستخدمة هي البحث المكتبي من خلال جمع المراجع والمصادر ذات الصلة, ثم قام  بتحليلها واستنتاجها. أوضحت نتائج  البحث: أن اختيارات أبو داود سليمان بن النجاح  فى رسم المصحف موجود في القواعد الستة التي تضمنت فى قاعدة الحذف والزيادة والإبدال والهمزات والوصل والفصل و وقاعدة القراءتين وكتب على إحداهما. وتحتوي تلك الإختيارات  بشكل عام حول: 1) اختيار الحذف فضلا من الإثبات  2) اختيار الإثبات فضلا من الحذف ، 3) اختيار إلى  آراء مشهورة و أكثر الإستعمال ، 4) اختيار بسبب أوزان الكلمة المناسبة والمعيّنة ، 5) اختيار بسبب أصل الكلمة ، 6 ) إتباع على رأي أستاذه  - الداني ، 7) اختيار بنظر إلى بعض المخطوطات القديمة و  وموافقته إلى أكثر المصاحف العتيقة ، 8) اختيار بسبب وجود الرواية وبعض القراءات المسندة ، 9) اختيار بسبب التوافق بين اللّفظ مع رسمه ، 10) اختيار بسبب الأحسن والأجمل الأفضل فى تخطيط رسمه . الكلمات المفتاحية : اختيارات, أبو داود, قواعد رسم المصحفAbstractThis research is to analize preference of Abu Dawud Sulaiman bin Najjah in rules of rasm al-mushaf, analyzed from his monumental work, i.e“Mukhtasar al-Tabyin li Hija’ al-Tanzil”. In rasm al-Mushaf, his conception and attainments serve as the main reference (masdar asasi in deciding most copy patterns and letter or word writing in al-Quran  which is admittedly quite difficult and complicated, even when compared with his teacher’s attainments (Abu ‘Amar al-Dani - al-Muqni) not a little bit from his view is different with rules of rasm al-Mushaf. One of the excellence of his attainments (al-Tanzil) because it is arranged in tahlili from surah al-Fatihah up to al-Nas so it’s quite traced, detailed, comprehensive and considered easy in referring to the technical writing of al-Quran. This research is a study of figures and his creation so the method used in this research is library research by collecting related literature, then analyze and conclude it. The result shown that preference of Abu Dawud Sulaiman bin al-Najjah found in six rules of rasm, which covers rules of al-hazf, al-ziyadah, al-ibdal,  al-hamazat, al-wasl wa fasl, and qira’atani wa kutiba ‘ala ihdahuma. In general, preferences range from : 1) Choosing hazf  rather than isbat 2) Choosing isbat  rather than  hazf, 3) Choosing a more famous opinion, 4) Choosing for reasons to adjust certain words, 5) Choosing because seeing the origin of a word, 6) Following the opinions of his teacher (al-Dani), 7) Selecting and referring to certain ancient Manuscripts, 8) Choosing the writings because of the existence of history and certain reading, 9) Choosing because of compatibility between speech and writings, 10) Choosing because of his fondness for beauty, subtlety and virtue the pattern of rasm.